Numerical Study on the Optimization Design of Photovoltaic/Thermal (PV/T) Collector with Internal Corrugated Channels - Xiangrui Kong; Yuhan Zhang; Jinshun Wu; Song Pan (International Journal of Photoenergy)
This study presents a theoretical study on the super thin and conductive thermal absorber with built-in corrugated channels on the basis of previous field experiments. The flow and heat transfer characteristics of the corrugated channels are simulated to identify the factors affecting photovoltaic/thermal (PV/T) system efficiency. The influences of the structural parameters such as the corrugation number, the corrugation area, and the flow channel width on the water outlet temperature and heat collection are discussed in order to support the structural optimization design of the hybrid PV/T system. The simulation results were validated to be in good agreement with experimental results. The results indicate that increasing inlet water velocity leads to a decrease in the outlet temperature. It was found that the corrugation area and the flow channel width have impacts on the outlet temperature of the hybrid PV/T collector panel. When the flow channel width of the absorber plate is reduced from 4 mm to 3 mm, the outlet temperature attained is between 298 and 302 K, and the heat collection is in the range of 16.2–51.4 MJ/h. This led to an increase in the amount of heat collected by 18.6%.